Engineering education in islamic world: Challenges and objectives - Hameed, Shihab A. (2012)
Higher education system is a driving factor for development. Knowledge seeking and education are essential acts in Muslims’ life. Having an efficient and effective engineering education in Islamic world is essential to graduate a qualified skilled engineers to lead development and bridging the gap (scientific, Industrial, economical, etc) with developed countries. Integrating and implementing Islamic principles in all aspects of engineering education leads to produce a qualified engineers professionally (employability skills) and ethically. This paper introduces the main challenges and weaknesses facing the engineering education process. It proposes set of recommendations to strength engineering education. Having effective future plans for engineering education in Islamic world will lead to improve qualification of graduations, communities, organizations, societies, and Islamic world at all. Higher institutions have to cooperate and implement Islamic-based policies and practices to create proper and supportive educational environments for their stakeholders (students, faculty, administrators, and employers) that lead to strengthen the future of Islamic World.